Design of Appropriate Technology Based on Waste Treatment Equipment Using Value Engineering Method in Kedung Turi - Sultan Afli; Boy Isma Putra (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
The purpose of this research is to create a waste burner using raw materials from factory welding waste. The method used in this research is the value engineering method. In Gununggansir Village, there is an increase in waste, one of which is in Kedung Turi Hamlet, which is very significant, causing a buildup of garbage and inadequate waste management in Gununggangsir Village. This is an alternative that is made is an environmentally friendly waste incinerator. The process of making a garbage incinerator has the advantage of being environmentally friendly by using used goods that are not used and can still be used. In this research, what will be done is utilizing used goods that have value and function to achieve a target value. The result of using this used material is that it saves the cost of making Trush Burner which was originally worth Rp. 1,626,000 to Rp. 965,000.